Fatigue Damage Assessment of a Metro Vehicle Bogie Frame Based on Measured Field Load - Yangmin Wu; Zunsong Ren (Machines)
As the operating conditions of metro vehicles become more complex, the fatigue damage of metro bogie frames under actual operating conditions becomes increasingly difficult to evaluate realistically. After a period of operation of metro trains, the load excitation on the frame and its vibrations become more intense, which causes elastic resonance and leads to fatigue damage. Therefore, it is of high importance to establish test load conditions that match the actual operating environment to conduct fatigue reliability research on frames. To address this problem, in this study, we developed a high-precision force measurement frame and performed a long-term field test. The load optimization factor was used to quantify the load amplitude amplification near the modal frequency caused by the frame elastic resonance. The real load conditions and damage conditions of the fatigued weak position were obtained. Additionally, the square of the difference between the damage calculated via the load spectrum and the measured damage was used as the objective function; the calibrated test load spectrum fully covered the fatigued weak position damage as the constraint condition. The load spectrum calibration coefficient was obtained via multi-objective optimization through a genetic algorithm. The results showed that the damage calculated using the calibrated load agreed well with the real damage, and the ratio of the equivalent stress amplitude between the two was in the range of 1–2. The calibrated test load spectrum obtained in this study can be used for the structural optimization and fatigue reliability design of the later frame. The findings reported here can also be applied to other dynamic systems where fatigue failure is a critical issue.